Structure/function analysis of spinalin, a spine protein of Hydra nematocysts - Hellstern, Simon; Holstein, Thomas W.; Özbek, Suat (The FEBS journal, 2006)
The nematocyst capsules of the cnidarians are specialized explosive organelles that withstand high osmotic pressures of ≈15 MPa (150 bar). A tight disulfide network involving cysteine-rich capsule wall proteins, like minicollagens and nematocyst outer wall antigen, characterizes their molecular composition. Nematocyst discharge leads to the expulsion of a long inverted tubule that was coiled inside the capsule matrix before activation. Spinalin has been characterized as a glycine-rich, histidine-rich protein associated with spine structures on the surface of everted tubules. Here, we show that full-length Hydra spinalin can be expressed recombinantly in HEK293 cells and has the property to form disulfide-linked oligomers, reflecting its state in mature capsules. Furthermore, spinalin showed a high tendency to associate into dimers in vitro and in vivo. Our data, which show incomplete disulfide connectivity in recombinant spinalin, suggest a possible mechanism by which the spine structure may be linked to the overall capsule polymer.